Soft-wars: A Capital-as-Power Analysis of Google's Power Trajectory - Christopher Mouré (Review of Capital as Power, 2021)
The capital as power framework, developed by Jonathan Nitzan and Shimshon Bichler, argues that the aim of business is not `profit maximization' but the differential accumulation of social power. Using this framework as a theoretical starting point, I analyze the differential accumulation strategies of Google and Microsoft. I present qualitative and quantitative evidence demonstrating that, despite the fact that Google and Microsoft currently derive the majority of their profits from separate businesses (and so by conventional logic are not in direct competition with one another), the two firms are nonetheless engaged in antagonistic competition over control of the computing industry.
Keywords: P16; P26; P48; G3; L86; L2; D2; D3; D4; 330; capitalization; corporation; differential accumulation; Facebook; Google; Microsoft; profit; technology